PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, PERSEPSI KEGUNAAN, DAN PERSEPSI KESENANGAN TERHADAP LOYALITAS NASABAH MOBILE BANKING - Risde, Kahti Ramadhia; Kurniawati, Kurniawati (Universitas Prof. Dr. Hazairin SH, 2023)
This research aims to prove the influence of perceived ease of use, perceived usefulness, and perceived enjoyment on satisfaction, then prove the influence of satisfaction on loyalty which is mediated by users' love for mobile banking. The type of research carried out was hypothesis testing which was analyzed using the Structural Equation Modeling (SEM) tool with the AMOS program. The research sample taken using a purposive sampling technique with individual analysis units. Primary data collected by distributing questionnaires to 262 respondents. The research results show that there is a positive influence of perceived ease of use, perceived usefulness, and perceived enjoyment on brand satisfaction, there is a mediating role of brand love in the influence of brand satisfaction on brand loyalty. This research is limited to customers who use mobile banking from banks in KBMI IV. Future researchers can examine customers who use mobile banking from banks in general. This research contributes to providing input to the top management of banks in Indonesia regarding what factors can help increase and manage customer loyalty, especially when using mobile banking.